A Landscape of the Genomic Structure of Cryptococcus neoformans in Colombian Isolates - Luz Helena Patiño; Marina Muñoz; Angie Lorena Ramírez; Nórida Vélez; Patricia Escandón; Claudia-Marcela Parra-Giraldo; Juan David Ramírez (Journal of Fungi, 2023)
Cryptococcus neoformans species complexes are recognized as environmental fungi responsible for lethal meningoencephalitis in immunocompromised individuals. Despite the vast knowledge about the epidemiology and genetic diversity of this fungus in different regions of the world, more studies are necessary to comprehend the genomic profiles across South America, including Colombia, considered to be the second country with the highest number of Cryptococcosis. Here, we sequenced and analyzed the genomic architecture of 29 Colombian C. neoformans isolates and evaluated the phylogenetic relationship of these strains with publicly available C. neoformans genomes. The phylogenomic analysis showed that 97% of the isolates belonged to the VNI molecular type and the presence of sub-lineages and sub-clades. We evidenced a karyotype without changes, a low number of genes with copy number variations, and a moderate number of single-nucleotide polymorphisms (SNPs). Additionally, a difference in the number of SNPs between the sub-lineages/sub-clades was observed; some were involved in crucial fungi biological processes. Our study demonstrated the intraspecific divergence of C. neoformans in Colombia. These findings provide evidence that Colombian C. neoformans isolates do not probably require significant structural changes as adaptation mechanisms to the host. To the best of our knowledge, this is the first study to report the whole genome sequence of Colombian C. neoformans isolates.